Implementasi Kurikulum Merdeka: Tantangan, Kebijakan, Dan Dampak Terhadap Pendidikan - T. Hasballah; Zulfatmi (Jurnal Ilmiah Edukatif, 2024)
This study focuses on the implementation of the "Merdeka Curriculum" in Indonesian schools, which aims to provide greater opportunities for fostering students' creativity and potential. This curriculum is expected to enhance the quality of education amidst various existing challenges. Although the Merdeka Curriculum holds great potential, its implementation faces obstacles such as teachers' readiness and competence, as well as limited educational infrastructure, particularly in remote areas. Government policy support is a key factor in its successful application. This research employs a qualitative approach through in-depth interviews with teachers, school principals, and education officials. Policy document analysis is also conducted to understand government strategies in supporting the implementation of the Merdeka Curriculum. The findings indicate that the Merdeka Curriculum positively contributes to students' creativity development. However, significant challenges include the preparedness of educators and unequal distribution of supporting facilities. Policies such as teacher training, the "Sekolah Penggerak" (Driving School) program, and strengthening educational facilities are considered helpful but still require further improvement. The implementation of the Merdeka Curriculum demands serious attention to continuous teacher training and equitable distribution of educational resources. It is recommended that the government conduct a comprehensive evaluation of existing policies and increase investment in educational infrastructure to ensure the curriculum's success across all regions of Indonesia.